2000
DOI: 10.1152/jappl.2000.89.3.1179
|View full text |Cite
|
Sign up to set email alerts
|

Reduced strength after passive stretch of the human plantarflexors

Abstract: The purpose of this study was to assess strength performance after an acute bout of maximally tolerable passive stretch (PS(max)) in human subjects. Ten young adults (6 men and 4 women) underwent 30 min of cyclical PS(max) (13 stretches of 135 s each over 33 min) and a similar control period (Con) of no stretch of the ankle plantarflexors. Measures of isometric strength (maximal voluntary contraction), with twitch interpolation and electromyography, and twitch characteristics were assessed before (Pre), immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
539
19
115

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(736 citation statements)
references
References 37 publications
63
539
19
115
Order By: Relevance
“…The amplitude values (rms) were calculated for a time period (2.00 seconds and 0.22 second for 30 and 270Њ·s Ϫ1 , respectively) that corresponded to a 60Њ range 7 of motion from approximately 60-120Њ of flexion at the elbow. The muscle action with the highest peak torque was used as the representative score for both EMG and MMG at each velocity.…”
Section: Signal Processingmentioning
confidence: 99%
“…The amplitude values (rms) were calculated for a time period (2.00 seconds and 0.22 second for 30 and 270Њ·s Ϫ1 , respectively) that corresponded to a 60Њ range 7 of motion from approximately 60-120Њ of flexion at the elbow. The muscle action with the highest peak torque was used as the representative score for both EMG and MMG at each velocity.…”
Section: Signal Processingmentioning
confidence: 99%
“…Another theory to explain changes in performance through stretch modalities is that of changes in muscle stiffness. Static stretches have been shown to decrease the stiffness of the musculotendinous unit (MTU) (Avela et al 1999;Evetovich et al 2003;Kubo et al 2001;Rosenbaum andHennig 1995, Wilson et al 1991), leading to decreases in performance due to an alteration in the force-length relationship of a muscle (Fowles et al 2000). Static stretching may increase tendons' compliance which affects negatively jump performance due to the prolonged contact time and the non-effective transmission of energy during the stretch shortening cycle (SSC).…”
Section: Jpes ®mentioning
confidence: 99%
“…Although basketball coaches follow the aforementioned warm-up type, recent studies have examined the effect of static stretching during warm-up and found detrimental impact on performance (Faigenbaum et al 2006, Fletcher & Monte-Colombo 2010, Pearce et al 2009, Fowles et al 2000, Power et al 2004, Alikhajeh et al 2012, Little & Williams 2006, Chaouachi et al 2008, ο Nelson et al 2005, Sayers et al 2008, Fletcher & Jones 2004, Gelen 2010, Needman et al 2009, Winchester et al 2008Famisis 2015, Papadopoulos et al 2015. Reductions on vertical jump performance, lower limbs' power (Faigenbaum et al 2006, Fletcher & MonteColombo 2010, Pearce et al 2009), muscle strength (Fowles et al 2000;Power et al, 2004), power (Alikhajeh et al 2012, Little & Williams, 2006, acceleration (Chaouachi et al 2008, Nelson et al 2005, Sayers et al 2008)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Static stretching reduces strength [7][8][9][10][11] , which raise concerns to its use prior to physical activity. Because of this, ballistic stretching has tended to replace static stretching in modern practices of warm up 12 .…”
Section: Introductionmentioning
confidence: 99%